2017
DOI: 10.1111/pim.12494
|View full text |Cite
|
Sign up to set email alerts
|

Induction of haem oxygenase‐1 increases infection of dog macrophages by L. infantum

Abstract: We aimed to induce and inhibit HO-1, ascertaining its effect on infection rate, parasite load and the levels of superoxide, reactive oxygen species (ROS), nitric oxide (NO), TNF-alpha and IL-10 in cultured macrophages from healthy dogs infected by Leishmania infantum. Macrophages obtained from 15 healthy dogs were cultured alone or infected with L. infantum, with or without association of HO-1 inducer and inhibitor. The infection rate and the parasite load were determined by the number of infected macrophages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…L. donovani-improves control of pathogen replication in vivo in mice [223]. L. infantum chagasi-improves control of pathogen replication in vitro in dog macrophages [225]. T. cruzi-impairs control of pathogen replication in mice in vivo and in vitro in macrophages [231].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. donovani-improves control of pathogen replication in vivo in mice [223]. L. infantum chagasi-improves control of pathogen replication in vitro in dog macrophages [225]. T. cruzi-impairs control of pathogen replication in mice in vivo and in vitro in macrophages [231].…”
Section: Discussionmentioning
confidence: 99%
“…They further observed that treatment of cells with the HO-1 inducer CoPPIX results in impaired control of parasite replication associated with decreased superoxide, ROS and NO production. In the opposite direction, treatment with the HO-1 enzyme inhibitor SnPPIX resulted in a lower infection rate and decreased production of the anti-inflammatory cytokine IL-10 [225].…”
Section: Leishmaniasismentioning
confidence: 98%
“…HO-1 is thought to be an intracellular enzyme ( 27 ), and its detection in plasma would indicate substantial tissue damage. In this scenario, the release of HO-1 occurs after cellular lysis during robust inflammation associated with infectious diseases such as VL ( 21 , 28 , 29 ), tuberculosis ( 30 ) and malaria ( 31 , 32 ). For sand fly bite-induced HO-1 expression in the skin, our data demonstrates that it is triggered in resident skin macrophages by saliva and as such could play a critical role in the early establishment of Leishmania infection.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously described that serum concentrations of both total heme ( 13 ) and of HO-1 ( 12 ) are substantially elevated in patients with VL than in uninfected healthy endemic controls. Besides that, it has been shown that HO-1 induction favors L. infantum replication inside dog macrophages ( 39 ). In the present study, performed in the same patient population, we show that serum concentrations of total heme exhibit positive correlation with HO-1 and LDH levels while being negatively correlated with peripheral blood neutrophil counts, suggesting that systemic levels of heme are linked to parameters associated with increased VL disease progression.…”
Section: Discussionmentioning
confidence: 99%